CLIMATE CONDITIONS OF SURKHANDARYA PROVINCE, RESEARCH OBJECT AND METHODS - Kadirova DILBAR (Scholar Express Journal, 2022)
This article is written about the climatic conditions of Surkhandarya region, research object and methods. So, it is quite long from north to south. The province is surrounded by mountains on three sides, its border is open to the south, and its border with the country of Afghanistan through the Amudarya valley in the south is extremely curved according to the river bed. High mountains located on the western and north-western borders of Surkhandarya are factors that create special climatic conditions in the region.
Keywords: Surkhandarya; climate; sharoi; research